KAJIAN ASUPAN DAN STATUS GIZI PARA PEMULUNG DI TEMPAT PEMBUANGAN AKHIR (TPA) ALAK KOTA KUPANG - Magaringu, Eny M.; Jutomo, Lewi; Lada, Christina O. (Jurnal Pangan Gizi dan Kesehatan, 2011)
Scavengers are group of informal sector workers which require an optimal capacity of physics in completing their activities. Nutrient is one of the most important factors that influence physical capacity in daily activities. The nutrient is needed in maintaining the growth and development of the body and also provide sufficient energy in doing daily activities in order to increase work productivity. The aim of the research is to identify intake and the nutrient status of scavengers at the Alak landfill of Kupang city. The type of the research is a descriptive with the design of cross sectional study. The amount of sample is 37 people taken by means of total sampling method. The result of the research shows that (1) energy and protein intakes have discovered : the frequency of food distribution of most scavengers (56.76%) are in low category and 43.24% are in good category. The type of food consumed by all scavengers (100%) are in less category. The average intake of energy and protein of scavengers are 1656.95 kcal and 24.04 g. (2) Based on Body Mass Index (BMI), most (56.76%) scavengers are in the underweight category and 43.24% are in the normal category.